Family Models Between "Reality" and Advertising Stories - Boero, Marianna (E|C, 2020)
This paper deepens the relationship between narration and “reality” analysing the way in which the family, in its various expressions, is “recounted” and, in a social-semiotic perspective, “constructed” by advertising. In fact, as with other media discourses, advertising contributes to the creation of a common-sense imagery in which “working”, “family”, “childhood”, “male” and “female” models are provided. Through the proposal of such models, advertising texts communicate values, create familiar worlds, but do not always reflect what is happening in society. The model described is in fact the one of the “traditional” family, while there are still few advertisements that represent the different realities that still characterise contemporary societies. There is a prudence in advertising, which shows a tendency to preserve and thus a “slow pace” in adapting to social change.